Coating bacteria for anti-tumor therapy - Wang, Jiahui; Guo, Ning; Hou, Weiliang; Qin, Huanlong (Frontiers in Bioengineering and Biotechnology, 2022)
Therapeutic bacteria have shown great potential on anti-tumor therapy. Compared with traditional therapeutic strategy, living bacteria present unique advantages. Bacteria show good self-propulsion, high motility and great colonization ability in tumor microenvironment, where is hypoxic, nutritious and immunosuppressive. Bacterial-medicated antitumor therapy has been successfully applied on the treatment of mouse melanoma, colorectal cancer and so on, but the low therapeutic effect and biosafe limit its application on clinical treatment. With the development of material science, coating living bacteria with suitable materials has received widespread attention to achieve synergetic therapy on tumor. In this review, we summarize various materials for coating living bacteria in cancer therapy and envision the opportunities and challenges of bacteria-medicated antitumor therapy.